Defining Rail Track Input Conditions Using an Instrumented Revenue Vehicle. (2017) - Chong, T.L.; Awad, M.N.; Nadarajah, N.; Chiu, W.K.; Lingamanaik, S.N.; Hardie, G.; Ravitharan, R.; Widyastuti, H.
Abstract: To model the dynamic response of a train running over a given length of rail, the input conditions must be adequately defined. This paper explores the use of an instrumented rail vehicle to assist in the definition of this input condition. The benefits of using instrumented rail vehicle for condition assessment of track and rolling stock are gaining popularity. Railway track and rolling stock condition monitoring is essential in ensuring the safe and efficient function of railway systems. The ability to use an instrumented revenue vehicle for the condition assessment of rail tracks is particularly significant because this capability will not require track access during inspection. This instrumented vehicle can also provide useful data for the definition of the rail track input conditions for the assessment of the stability of a rail vehicle when traversing along the track. This information can be used to establish the wagon speed limits to ensure safe operation of the asset. To be able to predict the dynamic response of a rail vehicle, the dynamic input conditions imposed by the track will need to be identified. This paper will discuss some initial studies on the use of an instrumented rail vehicle to define the input conditions imposed by the rail track. The ability to define the rail input conditions is demonstrated by associating the results with features on the track that are identifiable.